Application of time domain nuclear magnetic resonance (TD‐NMR) for study of the distillation curve of petroleum. (20th October 2022) - Montes, Luciana F.; Morgan, Vinícius G.; Kock, Flávio V. C.; Castro, Eustáquio V. R.; Barbosa, Lúcio L.
Abstract: Crude oil distillates are a highly useful industrial product, mainly for energy generation. Unfortunately, they are rarely studied, mainly due to the low accessibility to products directly obtained from the distillation process, which is a laborious, expensive, and time‐consuming operation. This work presents and discusses the use of time‐domain nuclear magnetic resonance (TD‐NMR) as a simple, affordable, and straightforward tool for the development of correlations supported on the transverse relaxation time (T2 ) and boiling temperature. The results point out a high convergence between TD‐NMR experimental data and the ASTM D2892 method for distillates from light, medium, and heavy oils, with up to 52.20% of accumulated mass and boiling point temperature ( T b ) up to 400°C. Furthermore, an unprecedented relationship between T2 values and the accumulated mass of the distillates is first demonstrated. This new insight opens new perspectives for future prediction of accumulated mass for unknown crude oils, placing the TD‐NMR relaxometry as an appeal spectroscopy approach with a potential to meaningfully contribute to the daily refining petrochemical industry field operations. Abstract : Time domain NMR allowed a good correlation with ASTM D2892 method for distillates produced up to 400°C. Transverse relaxation time (T2 ) was used to build the distillation curves. Time domain NMR proved be fast, simple, and nondestructiveness technique.